1999
DOI: 10.1210/er.20.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Coregulators: Cellular and Molecular Biology

Abstract: Nuclear receptor coregulators are coactivators or corepressors that are required by nuclear receptors for efficient transcripitonal regulation. In this context, we define coactivators, broadly, as molecules that interact with nuclear receptors and enhance their transactivation. Analogously, we refer to nuclear receptor corepressors as factors that interact with nuclear receptors and lower the transcription rate at their target genes. Most coregulators are, by definition, rate limiting for nuclear receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
702
0
15

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 860 publications
(724 citation statements)
references
References 0 publications
7
702
0
15
Order By: Relevance
“…Thus suggesting other components of the oestrogen signalling pathway may be altered. Recent observations using laboratory models (Hall and McDonnell, 1999;Lanz et al, 1999;McKenna et al, 1999;Montano et al, 1999) have demonstrated that altered levels of OR isoforms and/or alteration of expression of coactivators and corepressors can deregulate oestrogen and antioestrogen activity in target cells, suggesting the hypothesis that altered levels of OR isoforms and/or coregulators in vivo could be a mechanism of tamoxifen resistance. Previously we have demonstrated that the relative expression of ORa/ORb as well as the relative expression of some OR coactivators to corepressors is significantly altered during breast tumourigenesis in vivo Murphy et al, 2000).…”
mentioning
confidence: 99%
“…Thus suggesting other components of the oestrogen signalling pathway may be altered. Recent observations using laboratory models (Hall and McDonnell, 1999;Lanz et al, 1999;McKenna et al, 1999;Montano et al, 1999) have demonstrated that altered levels of OR isoforms and/or alteration of expression of coactivators and corepressors can deregulate oestrogen and antioestrogen activity in target cells, suggesting the hypothesis that altered levels of OR isoforms and/or coregulators in vivo could be a mechanism of tamoxifen resistance. Previously we have demonstrated that the relative expression of ORa/ORb as well as the relative expression of some OR coactivators to corepressors is significantly altered during breast tumourigenesis in vivo Murphy et al, 2000).…”
mentioning
confidence: 99%
“…Nuclear receptors naturally interact with corepressors, which function to repress transcription when no ligand is bound. 28 BXRb may not interact properly with human corepressors, which is a limitation of this system. The RE, RLE and scER TF ZF s are of human origin and do not have this issue, and are therefore able to utilize VP64 and KRAB to assist in the up-and downregulation of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear receptors such as ERα and MR require coactivator proteins to stimulate the expression of their respective target genes [23;24], and experiments were therefore conducted to determine if MBG treatment influenced the expression of a major family of nuclear receptor coactivators, the steroid receptor coactivator family [25]. Experiments were also performed to determine whether exposure of cells to MBG affected the ability of aldosterone to promote interactions between MR and coactivator.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional activity of the MR, as for other members of the nuclear receptor superfamily, is positively influenced by coactivator molecules which are necessary for receptor interactions with the general transcriptional machinery [25]. The coactivator SRC-3 (also known as AIB1 or RAC3) interacts with the ligand binding domain of agonist-bound steroid receptors and helps to recruit additional factors such as CBP and PCAF which ultimately results in chromatin remodeling, recruitment of RNA polymerase II and activation of gene expression.…”
Section: Resultsmentioning
confidence: 99%